Categorization of venoms according to bonding properties: An immunological overview. (February 2016) - Ibrahim, Nihal M.; El-kady, Ebtsam M.; Asker, Mohsen S.
Highlights: Cross-reactivity among venoms was studied in scope of bonding properties between antigens and antibodies. Homologous interactions are mainly mediated by high avid antibodies. Low avid antibodies are involved in heterologous interactions. A new indicator of bonding strength was used to categorize venoms to the donor animal family. The use of NH4 SCN in ELISA creates more specific conditions to take place and prevents lower avid antibodies to share. Abstract: In this report, we present a study on the antigenic cross-reactivity of various venoms from the most dangerous Egyptian snakes and scorpions belonging to families Elapidae, Viperidae and Buthidae. The study was carried out with special reference to bonding properties between venoms and antivenoms and their involvement in the formation of specific and/or cross-reactive interactions. The homologous polyclonal antivenoms showed high reactivity to the respective venoms and cross-reacted with varying degrees to other non-homologous venoms. Assorting the antivenoms according to their susceptibility to dissociation by different concentrations of NH4 SCN revealed that most of the antibodies involved in homologous venom–antivenom interactions were highly avid; building up strong venom–antivenom bonding. Whereas cross-reactions due to heterologous interactions were mediated by less avid antibodies that ultimately led to the formation of venom–antivenom bonding of different power strengths depending on the antigenic similarity and hence on the phylogenetic relationship of the tested venom. A new parameter evaluating high and low avid interactions, designated as H/L value, for each antigen-antibody bonding was initiated and used as an indicator of bonding strength between different venom–antivenom partners. H/L values were many folds higher than 1 for homologous and closely related venoms, 1 or around 1 for cross-reactive venoms, whereas venoms from unrelated remote sources recorded H/L values far less than 1. Using well defined polyclonal antivenoms, H/L value was successfully used to assign eight unknown venoms to their animal families and the results were confirmed by species-specific ELISA and immunoblotting assays.